IMPLEMENTASI KEBIJAKAN PENYELENGGARAAN TRANSPORTASI TENTANG PENGUJIAN KENDARAAN BERMOTOR DI DINAS PERHUBUNGAN KABUPATEN BANDUNG - Feri Safuan (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
So far, the government has implemented a policy for tackling the impact of the use of motor vehicles one of which is the policy in the public service in the manufacture of motor vehicle testing. Department of Transportation as the implementer of policy areas rated yet to change signifikan.Tujuan this study is to analyze and determine the implementation of the policy on motor vehicle testing service (Kier) conducted Bandung District Department of Transportation The theory used to guide research is theory policy implementation. This research approach using qualitative research methods to study descriptive design, results showed that implementation of the policy on motor vehicle testing service has not done well, Seen from the conclusion that the service is not yet optimal in implementing motor vehicle permit (Kir) by Bandung District Department of Transportation due by factors which consist of: (a) Standards and Targets policy / size and policy objectives; (B) Resources; (C) Characteristics of the implementing organization; (D) Communications between organizations (e) The disposition or attitude of the implementers (f) The social environment, economic and political